2014
DOI: 10.1021/jp5082752
|View full text |Cite
|
Sign up to set email alerts
|

Key Role of End-Capping Groups in Optoelectronic Properties of Poly-p-phenylene Cation Radicals

Abstract: Poly-p-phenylenes (PPs) are prototype systems for understanding the charge transport in π-conjugated polymers. In a combined computational and experimental study, we demonstrate that the smooth evolution of redox and optoelectronic properties of PP cation radicals toward the polymeric limit can be significantly altered by electron-donating iso-alkyl and iso-alkoxy end-capping groups. A multiparabolic model (MPM) developed and validated here rationalizes this unexpected effect by interplay of the two modes of h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
138
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
2

Relationship

4
5

Authors

Journals

citations
Cited by 66 publications
(142 citation statements)
references
References 41 publications
4
138
0
Order By: Relevance
“…For this purpose, we utilized the B1LYP-40 functional [i.e. B1LYP-40/6-31G(d)+PCM(CH 2 Cl 2 )] 19,20 because our recent careful benchmarking studies on a number of polyaromatic systems 17,2022 showed that this functional allows an accurate description of the spin/charge (hole) distribution in their cation radicals, and, in turn, the prediction of the corresponding redox/optical properties ( E ox1 , ν D0→D1 ) with high fidelity to experimental data. The excellent performance of the B1LYP-40 functional owes to the fact that 40% contribution of the exact (i.e.…”
Section: Resultsmentioning
confidence: 99%
“…For this purpose, we utilized the B1LYP-40 functional [i.e. B1LYP-40/6-31G(d)+PCM(CH 2 Cl 2 )] 19,20 because our recent careful benchmarking studies on a number of polyaromatic systems 17,2022 showed that this functional allows an accurate description of the spin/charge (hole) distribution in their cation radicals, and, in turn, the prediction of the corresponding redox/optical properties ( E ox1 , ν D0→D1 ) with high fidelity to experimental data. The excellent performance of the B1LYP-40 functional owes to the fact that 40% contribution of the exact (i.e.…”
Section: Resultsmentioning
confidence: 99%
“…The equilibrium concentrations of the species in eqs (8) and (9) can be determined from the equations of chemical equilibria and equations of mass and charge balance (eqs (11)(12)(13)(14)(15)) combined into a cubic equation of one variable (eq. (16)) in terms of oxidant concentration [Ox +• ], which can be solved either analytically or numerically.…”
Section: Resultsmentioning
confidence: 99%
“…[4][5][6][7][8][9][10][11][12] Importantly, such redox titrations allow one to quickly ascertain not only the optical properties of D +• and D 2+ but may also provide the estimates of redox potentials without the need of a complex electrochemical setup. It is noteworthy that characterizations of redox centers in proteins involved in biochemical transformations invariably make use of redox titrations in water-containing ample electrolyte.…”
Section: +mentioning
confidence: 99%
“…Thus, in polymer solutions a distribution of conformers might be present, which may influence the fast dynamical electronic processes that occur in optoelectronic devices such as exciton diffusion or charge migration. [11][12][13][14][15][16][17][18][19][20][21] For this reason it is extremely difficult to gain insight into the relation of electronic processes in conjugated polymers and their microscopic or superstructure in solution and in the solid state. 22 Recently Scholes et al addressed this issue very elegantly by investigating MEH-PPV in its stretched form in CHCl 3 solution in comparison to its coiled nanoparticle form in aqueous solution.…”
Section: Introductionmentioning
confidence: 99%